Situs Hindu Pra-islam di Kudus dan Sikap Toleran Sunan Kudus - Moh Rosyid (UIN Sunan Gunung Djati Bandung, 2021)
Among historical sites in Kudus, Central Java is Langgar Bubrah, in which laying lingga and yoni, two symbols often found in a Hindu temple. Some archeologists consider this as proof of Sunan Kudus’s tolerance. This paper analyzes the preservation of religious sites and their relation to promote religious tolerance. Data were collected through interviews, observation, and documentation analysis is descriptive qualitative. The result shows that Sunan Kudus promoted tolerance among his people by preserving several old traditions such as preventing. However, the Kudus Regency Government has optimized tried to treat it, so it needs to be scheduled to rescue cultural objects, namely restoration, revitalization, and facilitating cultural facilities and infrastructure in the form of performance spaces. Kudus local parliament members also need to realize the budget politics in the regional budget, which favors cultural preservation by providing funding for cultural advancement based on investment considerations. The research to contribution for development archeology associated with culture heritage Hindu in Kudus pra-Islam.